2019
DOI: 10.3390/app9224941
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Freeze-Thaw Cycles on the Mechanical Properties and Parameters of the Duncan-Chang Constitutive Model of Remolded Saline Soil in Nong’an County, Jilin Province, Northeastern China

Abstract: In seasonally frozen areas, physical and mechanical soil properties change dynamically under the effect of the freeze-thaw cycles (FTCs), which is a problem that cannot be ignored in geotechnical engineering. In order to study the effect of the FTC on the strength and the mechanism of deformation and failure of saline soil, this paper took Nong’an saline soil as the research object. In total, 105 groups of remolded samples with different salt contents (S) after FTCs were examined in unconsolidated-undrained te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Therefore, considering the regional applicability of SNS, and according to Test Methods of Materials Stabilized with Inorganic Binders for Highway Engineering (JTG E51-2009) [23], the 10% SNS-S and the cement stabilized soil (CS-S) were put into a cryogenic chamber (−18 • C ± 2 • C) and a thermostatic water tank (20 • C ± 2 • C), respectively, for freeze-thaw cycles by simulating the climatic environment of alternating cold and hot. Finally, their antifreeze indexes were calculated by the loss strength before and after the freeze-thaw cycles [24,25].…”
Section: Freeze-thaw Cycle Testmentioning
confidence: 99%
“…Therefore, considering the regional applicability of SNS, and according to Test Methods of Materials Stabilized with Inorganic Binders for Highway Engineering (JTG E51-2009) [23], the 10% SNS-S and the cement stabilized soil (CS-S) were put into a cryogenic chamber (−18 • C ± 2 • C) and a thermostatic water tank (20 • C ± 2 • C), respectively, for freeze-thaw cycles by simulating the climatic environment of alternating cold and hot. Finally, their antifreeze indexes were calculated by the loss strength before and after the freeze-thaw cycles [24,25].…”
Section: Freeze-thaw Cycle Testmentioning
confidence: 99%
“…During the formation of soil, various physical and chemical interactions form associations between particles that provide structural strength, and soil with structural strength is called structural soil [1,2]. The structural strength of soil causes differences in the engineering properties of undisturbed and remolded soils [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…analyzed the volumetric strain, stress-strain, and shear strength of fine-grained, complex, mixed saline soils containing NaCl and Na 2 SO 4 at low temperatures [29]. Some researchers also explored the effects of FCTs and salt solution (Na 2 SO 4 and NaHCO 3 ) contents on the shear properties of mixed saline soil in the Songnen Plain, Northeast China [30][31][32]. It was found that the transportation of soil water and salt of saline soil was affected by temperature, and the FTCs increased the ion exchange capacity.…”
Section: Introductionmentioning
confidence: 99%